Regulatory T cells in rheumatoid arthritis showed increased plasticity toward Th17 but retained suppressive function in peripheral blood. Issue 6 (12th February 2014) - Wang, Tian; Sun, Xiaolin; Zhao, Jing; Zhang, Jing; Zhu, Huaqun; Li, Chun; Gao, Na; Jia, Yuan; Xu, Dakang; Huang, Fang-Ping; Li, Ningli; Lu, Liwei; et al.
Abstract : Objective: Regulatory T cells (Tregs) with the plasticity of producing proinflammatory cytokine IL-17 have been demonstrated under normal and pathogenic conditions. However, it remains unclear whether IL-17-producing Tregs lose their suppressive functions because of their plasticity toward Th17 in autoimmunity. The aim of this study was to investigate IL-17-producing Tregs from patients with rheumatoid arthritis (RA), and characterise their regulatory capacity and clinical significance. Methods: Foxp3 and IL-17 coexpression were evaluated in CD4 T lymphocytes from RA patients. An in vitro T cell polarisation assay was performed to investigate the role of proinflammatory cytokines in IL-17-producing Treg polarisation. The suppressive function of IL-17-producing Tregs in RA was assessed by an in vitro suppression assay. The relationship between this Treg subset and clinical features in RA patients was analysed using Spearman's rank correlation test. Results: A higher frequency of IL-17-producing Tregs was present in the peripheral blood of RA patients compared with healthy subjects. These cells from peripheral blood showed phenotypic characteristics of Th17 and Treg cells, and suppressed T cell proliferation in vitro. Tregs in RA synovial fluid lost suppressive function. The Th17 plasticity of Tregs could be induced by IL-6 and IL-23. An increased ratio of this Treg subset was associated with decreased levels of inflammatory markers, including the erythrocyte sedimentation rate and C-reactive protein level, in patients with RA. Conclusions: Increased levels of IL-17-producing Tregs were identified in RA patients. This Treg subset with Th17 plasticity in peripheral blood retained suppressive functions and was associated with milder inflammatory conditions, suggesting that this Treg population works as a negative regulator in RA, but in RA synovial site it may be pathogenic.